ANALISIS FAKTOR PENDUKUNG PENINGKATAN KINERJA PEGAWAI BADAN PUSAT STATISTIK KABUPATEN LABUHANBATU - Elida F. S. Simanjorang; Christine Herawati Limbong; Nova Jayanti Harahap (Universitas Bunda Mulia, 2021)
Supporting factors that are presented are the quality of human resources, work competence, and work commitments analyzed how they affect the performance of employees of Badan Pusat Statistik (BPS) Kabupaten Labuhan Batu, both partially and simultaneously. Data collection uses interviews, questionnaires and literature study. Work on data analysis methods using SPSS 22.0 for Windows software. This study used a sample of 30 employees taken using total sampling techniques. The results of the study based on the F test showed that the quality of human resources, work competence and work commitment simultaneously had a positive and significant effect on the performance of Badan Pusat Statistik (BPS) Kabupaten Labuhan Batu employees, where the value of Fcount (17.583)> Ftable (2.98) with a significance level of 0.000 < 0.05. T-test results show that the quality of human resources (X1) has a positive and significant effect on the performance of Badan Pusat Statistik (BPS) Kabupaten Labuhan Batu employees, where the tcount (2.382)> ttable (1.706) and the significance value of 0.025 <0.05, work competence ( X2) positive and significant effect on the performance of Badan Pusat Statistik (BPS) Kabupaten Labuhan Batu employees, where the tcount (4.704)> ttable (1.706) and the significance value of 0.000 <0.05 and work commitment (X3) also have a positive and significant effect on the performance of the employees of Badan Pusat Statistik (BPS) Kabupaten Labuhan Batu, where the tcount (3.860)> ttable (1.706) and the significance value of 0.001 <0.05. Adjusted R Square value of 0.632 means that employee performance can be explained by the quality of human resources, work competence, and work commitments of 63.2%, while the remaining 36.8% is explained by other factors not examined in this study.